Ecological Effects and Occupational Health Hazards Due to Coir Retting: A Case Study from West Coast of Kerala, India - M. Kadeeja Beevi, S. Sreekumar and Hiran Nazir K (Nature Environment and Pollution Technology An International Quarterly Scientific Journal, 2012)
The backwater of Kerala is becoming polluted due to persistent retting of coconut husk for the manufacture of coir. This paper assesses the ecological status of the retting ground and brings out the occupational health hazards due to coir retting. It is observed that the quality of water becomes deteriorated due to retting, and plankton and benthic fauna show low community diversity. The paper also highlights the occupational health hazards observed among the coir workers